Dentin phosphoprotein inhibits lipopolysaccharide-induced macrophage activation independent of its serine/aspartic acid-rich repeats. (February 2020) - Nakanishi, Jun; Suzuki, Shigeki; Yoshida, Kazuma; Hirata-Tsuchiya, Shizu; Haruyama, Naoto; Yamada, Satoru; Shiba, Hideki
Highlights: Dentin phosphoprotein (DPP) is the most abundant non-collagenous protein in dentin. DPP possesses anti-inflammatory effects on LPS-stimulated macrophages. DPP contains long serine/aspartic acid-rich repeats (SDrr) in its central portion. The variations in SDrr length are not correlated with the inhibitory ability of DPP. The anti-inflammatory medicinal possibilities of recombinant DPP have been proposed. Abstract: Objective: The objective of this study was to investigate the effects of dentin phosphoprotein (DPP) on lipopolysaccharide-induced inflammatory responses of macrophages in vitro . Design: Wildtype and mutant recombinant dentin phosphoprotein (rDPP) proteins were generated using a mammalian expression system. Macrophages, phorbol 12-myristate 13-acetate-differentiated THP-1 cells, were stimulated with lipopolysaccharide in the absence or presence of rDPP proteins. After the 24-hr incubation, the inflammatory gene expression levels were examined by quantitative reverse-transcription polymerase chain reaction and the amount of secreted TNF-α protein was evaluated by enzyme-linked immunosorbent assay. Furthermore, the subcellular localization of exogenously added rDPP was examined by immunocytochemistry, and the direct binding of rDPP to lipopolysaccharide was quantified by solid-phase binding assay. Results: rDPP dose-dependently reduced the expression of lipopolysaccharide-induced inflammatory genes, such as TNFα, IL-1β, and IL-8, and TNF-α protein secretion from the macrophages. Furthermore, mutant rDPP having a shortened serine/aspartic acid-rich repeats (SDrr) was also able to inhibit lipopolysaccharide-induced inflammatory responses of macrophages. rDPP was localized adjacent to the cellular membrane rather than in the cytoplasm, and rDPP was able to bind to lipopolysaccharide. These results suggested that rDPP inhibited lipopolysaccharide-induced inflammatory responses by binding to lipopolysaccharide. Conclusions: In addition to the well-known functions of DPP for dentin mineralization that depend on the SDrr, we demonstrated that DPP possesses anti-inflammatory effects on lipopolysaccharide-stimulated macrophages that are independent of the SDrr.